Model Pembelajaran bagi Lansia pada Pondok Pesantren di Indonesia - Suryadi Suryadi; Mustofa Kamil; Asep Saepudin; Iip Saripah; Yusmanto Yusmanto; Wawan Hardiyanto (Journal on Education, 2023)
Islamic Boarding School (Pesantren) is one of the religious educational institutions that do not only function as a place for the transfer of knowledge (transfer of knowledge), especially in religious sciences. Islamic boarding schools also carry out the mission of forming the character of students to become mature/perfect human beings. Especially for an elderly person who wants to get encouragement to be more active in worship in order to get a sense of security and calm. The learning model in Islamic boarding schools for the elderly is one form of strengthening the role of the family in caring for the elderly. This research is qualitative research with a literature review method to assist a researcher in providing an overview of the context, debate, or current issues. Sources of data in this study are journals, articles, books, and other relevant references. The data collection technique is done by literature study and documentation. The data analysis technique begins with accessing the data, organizing, sorting, categorizing, and classifying the collected documentation studies. The learning model for the elderly in Islamic boarding schools places more emphasis on direct learning models and character building through life experiences. Therefore, Islamic boarding schools need to pay attention to the background and needs of the elderly in preparing learning models so that the learning goals desired by learning participants can be achieved easily based on their respective beliefs, without being constrained by problems with physical conditions that are starting to be vulnerable and make every life experience a blessing. lessons in doing worship to Allah, God Almighty.